PENGETAHUAN ORANG TUA TENTANG KEJANG DEMAM PADA ANAK PRASEKOLAH DI PAUD NUANSA UDAYANA SILIGITA - Sumantri, W.Y; Asri Dewi, N.L.M; Artawan, I.K (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2021)
Background: Febrile seizure associated with a fever of 38oC or higher that triggers by the extracranial process without manifestation of neurologic dysfunction. The majority of parents suffer from stress and anxiety of febrile seizure occurrences. Adequate knowledge of febrile seizure is significant to provide initial medical care required during febrile seizure occurrences. Hence, this study aimed to know the knowledge level of febrile seizure on preschooler among parent in Nuansa Udayana Siligita Early Childhood Education School, Nusa Dua Badung. Method: A purposive sampling technique employed to select 123 study participants. Data collected by a questionnaire that distributed to the participant through the google-form platform. The analysis used is univariate. Results: Results revealed that the participant’s knowledge classified in the good, moderate, and low category with a total of 81 participants (79.0%), 22 participants (21.0%), and 0 participants (0.0 %), respectively. Conclusion: The level of knowledge of febrile seizure on preschoolers among parent Nuansa Udayana Siligita Early Childhood Education School classified in the good category. We suggest the parent improve their knowledge of febrile seizure to deliver initial proper medical care during febrile seizure occurrences or recurrences in their home or school.